INTEGRATION OF TRADITIONAL ECOLOGICAL KNOWLEDGE IN-TO PRIMARY SCHOOL LEARNING - Sumarwati Sumarwati; Sukarno Sukarno; Atikah Anindyarini; Dwi Winda Lestari (Universitas Negeri Makassar, 2020)
This research was conducted to understand the perception of people in Tawangmangu, Central Java in terms of the potential of teaching TEK in primary schools, challenges, and teaching strategies. We conducted semi-structured and unstructured interviews with 77 participants (local TEK experts, local communities, educators, and education officials). TEK in Tawangmangu includes folktales, ceremonies, offerings, typical food, terraced farming, intercropping systems, irrigation systems, crop management, herbal medicine, traditional house, and social system. Participants supported the idea because the TEK began to become extinct and identified its delivery in formal schools as a bridge to maintain it. Factors identified as obstacles are limited study time, limited access to subject matter, lack of political support, and differences in the characteristics of knowledge transfer between science and TEK. Participants claimed that the most appropriate strategy for teaching it in primary schools was to bring students closer to the real context. To teach it, the teacher chooses a number of contextual learning methods that are considered suitable, like field trips, role playing, task-based learning, and project-based learning.